Handbook of mindfulness and self-regulation - Ostafin, Brian D.; Robinson, Michael D.; Meier, Brian P. (Springer, 2015)
This empirically robust resource examines multiple ways mindfulness can be harnessed to support self-regulation, in part as a real-world component of therapy. Its authoritative coverage approaches complex mind/brain connections from neuroscience, cognitive, personality, social, clinical, and Buddhist perspectives, both within and outside traditional meditation practice. In domains such as letting go of harmful habits and addictions, dealing with depression and anxiety, regulating emotions, and training cognitive function, contributors show how mindfulness-based interventions encourage and inspire change. In addition to scientific coverage, experts translate their methods and findings on mindfulness mechanisms in terms that are accessible to students and clinicians. Included in the Handbook: Mindfulness and its role in overcoming automatic mental processes Burning issues in dispositional mindfulness research Self-compassion: what it is, what it does, and how it relates to mindfulness Mindfulness-based cognitive therapy and mood disorders Mindfulness as a general ingredient of successful psychotherapy The emperor's clothes: a look behind the Western mindfulness mystique Heralding a new era of mind/brain research...and deftly explaining our enduring fascination with mindfulness in the process...the Handbook of Mindfulness and Self-Regulation will enhance the work of scholars and practitioners...